Pengembangan Media Siduwan (Siklus Hidup Hewan) Berbasis Pop-Up Book Untuk Melatih Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Ipa Di Mis Hidayatussalam - Fadillah Putri Adeana; Pangulu Abdul Karim; Aufa (Nirta Learning Centre, 2025)
This research was conducted based on the fact that the current science learning process is still dominated by lecture methods and focused solely on teacher attention, thus lacking critical thinking skills. Therefore, it is necessary to develop learning media such as SIDUWAN (Animal Life Cycle) based on Pop-Up Books, which can help train students' critical thinking skills. This study aims to (1) determine the validity of the development of SIDUWAN (Animal Life Cycle) based on Pop-Up Books, (2) determine the effectiveness of the development of SIDUWAN (Animal Life Cycle) based on Pop-Up Books, and (3) determine the effectiveness of the development of SIDUWAN (Animal Life Cycle) based on Pop-Up Books. The method used in this study was Research and Development (R&D). The development was conducted using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 33 fourth-grade students. The results of the study show that: (1) The level of validity can be seen from the results of the media expert validation assessment of 100% (Very Valid), and the material expert validation of 95% (Very Valid), (2) The level of practicality is found from the results of the teacher response questionnaire of 100% (Very) and the results of the student response questionnaire of 94.24% (Very Practical), (3) The level of effectiveness can be seen from the results of the comparison of the Pre Test and Post Test scores. The average Pre Test score is 40.9, while the average Post Test score increased to 73.7. The N-Gain test shows a value of 0.56 with the category